Organizing for Coordination in the Public Sector
XIII, 283 p.
Keywords: This collection focuses on public sector coordination, key aspect of governments' have sought to tackle contemporary policy challenges. By guiding the reader through 20 case studies of novel coordination instruments from 12 countries, the compendium gives valuable lessons for achieving better coordination of public policies.